Points...: Interviews, 1974-1994 - Derrida, Jacques 1930-2004; Weber, Elisabeth; Weber, Elisabeth; Kamuf, Peggy -1947 (Standford Stanford University, 1995)
This volume collects twenty-three interviews given over the course of the last two decades by Jacques Derrida. It illustrates the extraordinary breadth of his concerns, touching upon such subjects as the teaching of philosophy, sexual difference and feminine identity, the media, AIDS, language and translation, nationalism, politics, and Derrida's early life and the history of his writings.
Keywords: Philosophy; Feminism